KONSEP HUKUM ISLAM DALAM PENANGGULANGAN DAN PERMASALAHAN DI INDONESIA - Hindun Umiyati; Lomba Sultan; Kurniati (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the Islamic law that regulates the behavior of Muslim life in all its aspects which consist of laws regarding ritual worship, political, criminal, civil, or legal rules in general. The Islamic legal system in Indonesia has the same and equal position as other legal systems that exist in Indonesia, namely customary law and western law. This research uses a normative-empirical method, namely by combining legal research methods that not only view the law as a prescriptive and applied discipline but also have a descriptive nature based on the reality of the development of law itself in society. There have been some phenomenal events. The application of Islamic law in Indonesia has a great opportunity because Islamic law has become a living law in society and has been integrated into the nation’s culture. Settlement of disputes/disputes that cannot be resolved by Islamic kinships such as tabayyun, islah, ta’awun, Qudwag hasanah, and others because of aspects that endanger life together, it is necessary to take firm and clear steps with the principle of harmony and the principle of propriety